The effect of terpenes on the life cycle of the malaria parasite - Mustapha, Obaidiyah (My University, 2017)
Malaria is a parasitic infectious disease resulting in high mortality rates especially in sub- Saharan Africa. Vector control and chemoprophylaxis are important aspects in the prevention of malaria. However, due to the emergence of resistance to antimalarial therapies and insecticides as a global issue, new compounds are required to ensure adequate therapy. For centuries, traditional phytomedicines have been used as effective malaria management. African traditional plants are commonly used in South Africa, where the essential oils (EOs) and extracts have been shown to possess promising activity in the control of malaria. As such, the activity of various EOs and essential oil constituents (EOCs) has been investigated on the lifecycle of the parasite. The in vitro parasite lactate dehydrogenase (pLDH) assay determined the antimalarial activity of the EO/EOCs on the asexual stages of the parasite. All five EOs, Artemisia afra, Lippia javanica, Cymbopogon citratus, Cymbopogon nardus and Ocimum basilicum displayed antimalarial activity, with C. citratus (IC50 value: 2.00 x10'5%) displaying the most activity in comparison to the control, quinine (IC50 value 1.71 x10"5%; 0.18 pM). Nine of the 22 selected EOCs displayed antimalarial activity with eucalyptol (IC50 value: 0.37 pM; 6.19 x10~6%) the most active. The sensitivity of the Anopheles vector was assessed by determining the larvicidal activity of the EO/EOCs. Larvicidal activity was displayed by all five EOs and 14 EOCs with LC5o values ranging from 0.001 to 0.047%. The EOCs, c/s-nerolidol and p-cymene displayed the most promising larvicidal activity of all tested EO/EOCs with LC5o values of 0.001 and 0.004%, respectively. When combined these two EOCs interacted in an additive manner (average IFIC: 0.94). It was also determined that the reconstituted crude oils made from the EOCs to replicate the original EO, displayed less larvicidal activities than the original EO. To determine the preliminary toxicological effect of the EO/EOCs, the haemolysis, lipid peroxidation inhibition, tetrazolium and brine shrimp lethality assays were undertaken. Haemolytic activity was not displayed by any of the EO/EOCs, with only O. basilicum and eugenol inhibiting lipid peroxidation. Cellular viability was affected by all five EOs (IC50 values: 2.4 x10"4 - 2.5 x10"1%) and fifteen of the selected EOCs (IC50 values: 0.2 - 72.4 pM). Cymbopogon citratus and C. nardus and ten EOCs possessed Artemia nauplii lethality activity (LC50 values: 6 x10‘7 - 1.4 x10"2%). Varying antimalarial, larvicidal and toxicological properties were observed for the various isomers of nerolidol, geraniol, pinene, linalool, thujone and citronellal. These results showed that the biological activities of the EO/EOCs have the potential to be used as adjuncts in the management of the malaria parasite and vector, as well as the development for novel drugs.
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in the fulfillment of the requirements for the degree of Master of Science in Medicine Johannesburg, South Africa, 2017
Keywords: Malaria; Malaria--genetics; Communicable Diseases--Epidemiology